OPTIMALISASI PERANGKAT HUMAS DI MEDIA SOSIAL YOUTUBE MADRASAH DI INDONESIA DALAM MENARIK MINAT CALON SISWA BARU TAHUN 2022 - Ravi Badriansyah Marpaung; Hasan Sazali (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2022)
This study aims to analyze the optimization of public relations tools on YouTube social media for Madrasah Senior High Schools in Indonesia to attract prospective students in 2022. Literature studies are used as a research method in this study. Research data is collected through the study or analysis of books, scientific works, articles or journals related to the articles written. The data analysis technique uses the Miles and Huberman model by using three parts of the analysis that go hand in hand: data reduction, data presentation and conclusion drawing/verification. The results of this study state that by optimizing public relations on the school's Youtube account, it is hoped that it will become a more effective and efficient bridge between the school and students, parents and the wider community. School YouTube also has functions in information, communication, and promotion media.